Watch case struck to mark the meeting of the IWMA when the 8 hour working day had been proclaimed as the Association's objective. From: 1/7 fol
Watch case struck to mark the meeting of the IWMA when the 8 hour working day had been proclaimed as the Association's objective. From: 1/7 fol.